Utilization of Coffee and Aren Cultivation in Producing Non-Alcoholic Wine-Flavored Aren Coffee Products to Improve the Economy of the People of Kutalimbaru, Deli Serdang - Deni Faisal Mirza; Devi Alvionita Alindra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This community service aims to utilize the cultivation of Coffee (Coffea Sp.) and Aren (Arenga Pinnata) plants in the manufacture of Aren Coffee with Non-Alcoholic Wine Flavor as an alternative to plants producing raw materials for innovative processed coffee products in Suka Makmur Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra. The benefits obtained are increasing positive acceptance responses in the Suka Makmur Village community so that this area becomes an alternative for the use of coffee and aren Aren plants as raw material for coffee innovation products. Non-Alcoholic Wine Flavor which can be a new variant of coffee product innovation and increase people's economic income, as well as increase people's knowledge and skills on how to make Non-Alcoholic Wine-Flavored Aren Coffee. The result of the program is the achievement of many understandings and perceptions from the people of Suka Makmur Village who agree and are enthusiastic about becoming a center for the development and planting of coffee and sugar Aren plants. The formation of a technical team for making Non-Alcoholic Wine Flavored Aren Coffee to produce a mainstay product in Suka Makmur Village. The formation of an “IT” team that produces video tutorials and a marketing team (how to make Non-Alcoholic Wine-flavored Aren Coffee and how to cultivate coffee and sugar Aren plants, as well as sell products on social media). Producing ready-to-drink processed products of three in one size of 20 gr, 100 gr, 250 gr, 500 gr and 1000 grams for sale thereby increasing the community's economic income and planting from the availability of 1000 seeds of coffee and sugar Aren plants to the community so that the forest in Suka Makmur Village becomes productive forest.